β-Asarone Ameliorates β-Amyloid–Induced Neurotoxicity in PC12 Cells by Activating P13K/Akt/Nrf2 Signaling Pathway - Meng, Miaomiao; Zhang, Lijuan; AI, Di; Wu, Hongyun; Peng, Wei (Frontiers in Pharmacology, 2021)
Accumulation of β-amyloid (Aβ) causes oxidative stress, which is the major pathological mechanism in Alzheimer’s disease (AD). β-asarone could reduce Aβ-induced oxidative stress and neuronal damage, but the molecular mechanism remains elusive. In this study, we used Aβ-stimulated PC12 cells model to explore the neuroprotective effects and potential mechanisms of β-asarone. The results showed β-asarone could improve cell viability and weaken cell damage and apoptosis. β-asarone also could decrease the level of ROS and MDA, increase the level of SOD, CAT and GSH-PX and ameliorate the mitochondrial membrane potential. Furthermore, β-asarone could promote the expression of Nrf2 and HO-1 by upregulating the level of PI3K/Akt phosphorylation. In conclusion, β-asarone could exert neuroprotective effects by modulating P13K/Akt/Nrf2 signaling pathway. β-asarone might be a promising therapy for AD.